1994
DOI: 10.1203/00006450-199404000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Energy Expenditure and Genotype of Children with Cystic Fibrosis

Abstract: FFM, fat-free mass SF, skinfold TBW, total body water FQ, food quotient RQ, respiratory quotient 2H 2 0 , deuterium oxide rC0 2 , mean daily CO 2 production Abbreviations CF, cystic fibrosis REE, resting energy expenditure TEE, total energy expenditure FVC, forced vital capacity FEV.. forced expiratory volume in 1 s FEF 25-75' forced expiratory flow between 0.25 and 0.75 s 2H, deuterium 180,oxygen-18 BW, body weight ABSTRACT. Increased energy expenditure, poor dietary intake, and fat malabsorption in patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
50
0
5

Year Published

1996
1996
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(62 citation statements)
references
References 18 publications
6
50
0
5
Order By: Relevance
“…However, importantly, this increase in REE was unrelated to menarche or the phase of the menstrual cycle. Many studies have described that children with CF have a higher REE than controls (Shepherd et al, 1988;Fried et al, 1991;Girardet et al, 1994;Tomezsko et al, 1994;Thomson et al, 1996;Zemel et al, 1996;Allen et al, 2003). Our finding that females with CF have a higher REE compared with controls is consistent with previous studies describing raised REE in females with CF (Zemel et al, 1996;Allen et al, 2003).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, importantly, this increase in REE was unrelated to menarche or the phase of the menstrual cycle. Many studies have described that children with CF have a higher REE than controls (Shepherd et al, 1988;Fried et al, 1991;Girardet et al, 1994;Tomezsko et al, 1994;Thomson et al, 1996;Zemel et al, 1996;Allen et al, 2003). Our finding that females with CF have a higher REE compared with controls is consistent with previous studies describing raised REE in females with CF (Zemel et al, 1996;Allen et al, 2003).…”
Section: Discussionsupporting
confidence: 92%
“…This has been confirmed by in vitro cell studies (Feigal and Shapiro, 1979) and by in vivo EE measurements of infants, children, adolescents and adults with CF (Shepherd et al, 1988;Fried et al, 1991;Girardet et al, 1994;Tomezsko et al, 1994;Thomson et al, 1996;Zemel et al, 1996;Allen et al, 2003). The evidence of whether the underlying disease or acquired factors (infection, lung disease) are the cause of this increased EE is not completely clear.…”
Section: Introductionmentioning
confidence: 89%
“…There is some evidence that this energy metabolism disorder is genetically conditioned (O'Rawe et al, 1992;Thomson et al, 1996), however the current study did not support this hypothesis. There was no relationship between REE and genotype, which is consistent with others (Fried et al, 1991;Tomezsko et al, 1994). Researchers have also suggested that the increase in REE is related to pulmonary function (Vaisman et al, 1987a,b;Buchdahl et al, 1988;Fried et al, 1991;Amin & Dozor, 1994), however this study did not ®nd any relationship between REE and FEV 1 or FVC.…”
Section: Discussionsupporting
confidence: 89%
“…Spicher et al, (1991) found no differences in the TEEaREE ratios between patients and controls. Tomezsko et al, (1994) also found no differences between pre-pubertal children with mild lung disease and CF and healthy controls, however they did ®nd a signi®cant difference between the DF508 homozygous subgroup and the mixed heterozygous group of patients. The current results did not demonstrate any differences in ECA between patients in different genotype subgroups.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation